Using the COMMVAC taxonomy to map vaccination communication interventions in Mozambique - Artur Manuel Muloliwa; Julie Cliff; Afiong Oku; Angela Oyo-Ita; Claire Glenton; Heather Ames; Jessica Kaufman; Sophie Hill; Yuri Cartier; Xavier Bosch-Capblanch; Gabriel Rada; Simon Lewin (Taylor & Francis Group, 2017)
Background: Improved communication about childhood vaccination is fundamental to increasing vaccine uptake in low-income countries. Mozambique, with 64% of children fully vaccinated, uses a range of communication interventions to promote uptake of childhood immunisation. Objectives: Using a taxonomy developed by the 'Communicate to Vaccinate' (COMMVAC) project, the study aims to identify and classify the existing communication interventions for vaccination in Mozambique and to find the gaps. Methods: We used a qualitative research approach to identify the range of communication interventions used in Mozambique. In-depth semi-structured interviews were carried out with key purposively selected personnel at national level and relevant documents were collected and analysed. These data were complemented with observations of communication during routine vaccination and campaigns in Nampula province. We used the COMMVAC taxonomy, which organises vaccination communication intervention according to its intended purpose and the population targeted, to map both routine and campaign interventions. Results: We identified interventions used in campaign and routine vaccination, or in both, fitting five of the seven taxonomy purposes, with informing or educating community members predominating. We did not identify any interventions that aimed to provide support or facilitate decision-making. There were interventions for all main target groups, although fewer for health providers. Overlap occurred: for example, interventions often targeted both parents and community members. Conclusions: We consider that the predominant focus on informing and educating community members is appropriate in the Mozambican context, where there is a high level of illiteracy and poor knowledge of the reasons for vaccination. We recommend increasing interventions for health providers, in particular training them in better communication for vaccination. The taxonomy was useful for identifying gaps, but needs to be more user-friendly if it is to be employed as a tool by health service managers.